«Romanos pero cristianos»: el proceso de «romanización» del cristianismo y las supuestas peculiaridades de la Iglesia de Hispania - Teja, Ramón (Hispania sacra, 2021)
Opposed to the traditional interpretation that Christianity prevailed in the Roman Empire because it managed to annihilate paganism, it is argued that more than annihilation there was a process of osmosis and assimilation between both “religious systems”. Within the framework of this process that the author calls “Romanization” of Christianity, there is the intention to refute the traditional interpretation, which dates back to Adolf von Harnack, of a supposed “rude worldliness and fanatical rigorism” that would have characterized the Spanish Church since the Antiquity.